Low dietary magnesium and fiber intakes among women with metabolic syndrome in Kuwait - Dalal U. Z. Alkazemi; Tasleem A. Zafar; Nourah Y. Alsouri; Abeer A. Aljahdali; Abeer A. Aljahdali; Stan Kubow (Frontiers in Nutrition)
IntroductionMetabolic syndrome (MetS) is a growing health concern among Kuwaiti women. Dietary magnesium and fiber have been implicated in reducing the risk of MetS; however, their specific effects on this population remain underexplored. This study aimed to investigate the association of dietary magnesium and fiber intake with the prevalence of MetS and its components among women in Kuwait.MethodsThis study included 170 women aged 18–65 (years) recruited from AL-Adan Hospital, Mubarak Hospital, and Riqqa Polyclinic. Data were collected using a modified Semi-Quantitative Food Frequency Questionnaire (SFFQ) to assess dietary intake, and biochemical measurements were performed to evaluate serum magnesium and other metabolic markers. MetS was diagnosed according to International Diabetes Federation (IDF) and Adult Treatment Panel III (ATP III) criteria. Statistical analyses included Mann–Whitney U-tests, chi-square tests, Spearman correlations, logistic and linear regression models, and Cohen’s kappa statistics.ResultsThe prevalence of MetS was 24 and 18% based on the IDF and ATP III criteria, respectively. Women with MetS had significantly lower dietary magnesium and fiber intakes than those in women without MetS (p < 0.001). A strong positive correlation was found among dietary magnesium intake, fiber intake, and serum magnesium levels (r = 0.957, p < 0.001 for magnesium; r = 0.917, p < 0.001 for fiber). Increased dietary magnesium and fiber intakes were linked to reduced odds of developing MetS and its components, except for blood pressure measurements. Cohen’s kappa demonstrated a strong agreement (K = 0.70, p < 0.001) between dietary and serum magnesium inadequacy.ConclusionIncreased dietary intakes of magnesium and fiber are associated with reduced odds of developing MetS among Kuwaiti women. These findings support the promotion of magnesium- and fiber-rich diets as preventive strategies against MetS.